Kewenangan Hakim dalam Mengadili Perkara Korupsi di Indonesia - Muniroh, Ira Nursafira (Universitas Pahlawan Tuanku Tambusai, 2025)
This article discusses the authority of judges in handling corruption cases and examines the role of evidence in the legal process of proof in Indonesia. In the Indonesian criminal justice system, the position of judges is crucial in ensuring the realization of justice through the authority to make independent decisions by considering valid evidence. This research is a legal research using a normative juridical approach and descriptive-qualitative methods. In addition, the data used in this study were obtained from books and journals relevant to the material discussed. This research shows that the independence and impartiality of judges are crucial elements in ensuring substantive justice. In addition, the effectiveness of the evidentiary system, including witness testimony, expert testimony, letters, instructions, and the defendant's testimony, also determines the legitimacy of judges' decisions. The results of the study confirm that strengthening the authority of judges and the consistent application of positive law are the main keys to eradicating corruption in Indonesia.